CREDIT AGREEMENTS IN COOPERATIVES BY DEFAULTING DEBTORS - Nugraha, Agus Bambang; Catturani, Ivanna (SYNTIFIC, 2024)
Background. This is motivated by the existence of cooperative activities in the savings and loan unit or what is known as a credit cooperative, this credit cooperative aims to help other fellow cooperatives, cooperative members, or the community in terms of capital to develop business by getting the loans needed with light terms according to the borrower's ability. However, in the implementation of the savings and loan agreement, there are several obstacles, especially in terms of default. The purpose of this study is to determine the implementation of a credit agreement with a defaulting debtor and how the settlement of defaulting debtors in a cooperative. Research Method. The method of this research approach is juridical-sociological, which means that research is carried out on the real situation of society with the intention and purpose of finding facts (fact-finding), which then leads to identification (problem-identification) and ultimately leads to problem-solution. Findings. During the execution of a loan agreement within a cooperative, it's essential to evaluate the loan-repaying capability of its members. If no family principles resolve the default, the cooperative sells the collateral to repay the debt. Conclusion. A savings and loan unit, or credit cooperative, provides loans with lenient terms to fellow cooperatives, members, or the community for business development. Defaults pose significant challenges in implementing savings and loan agreements.